2007
DOI: 10.1063/1.2432152
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal vortex shedding in a perturbed cylinder wake

Abstract: Cylinder wakes display distinct modes of vortex shedding when perturbed by appropriate means. By investigating experimentally the wake of a circular cylinder perturbed by a periodic fluctuation imposed on the inflow velocity, it is shown that bimodal behavior is possible. During a given experiment, the wake switches back and forth between two different vortex shedding modes, more specifically, a 2S↔2P transition is observed. No discernible change in the timing of vortex formation is found to accompany the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 19 publications
6
33
1
1
Order By: Relevance
“…3 that the first mode of the vorticity-based POD exhibits similar spatial features than those of the second mode. This is in good agreement with the results of Ma et al (2000), Dipankar et al (2007) and Konstantinidis et al (2007). Similar observations can be made for velocity-based POD.…”
Section: Podsupporting
confidence: 93%
See 1 more Smart Citation
“…3 that the first mode of the vorticity-based POD exhibits similar spatial features than those of the second mode. This is in good agreement with the results of Ma et al (2000), Dipankar et al (2007) and Konstantinidis et al (2007). Similar observations can be made for velocity-based POD.…”
Section: Podsupporting
confidence: 93%
“…The average vortex wavelength c = U c f s (U c is the convection velocity defined as 0.86U ∞ and f s is the vortex shedding frequency at x/d = 10 (Zhou et al 2002;Zhou and Antonia 1992) for both PODs is equal to 4.2d. Konstantinidis et al (2007) showed that a symmetric distribution of the POD modes with respect to the centerline reflects the antisymmetric characteristic of the flow field (with respect to the flow centerline). Consequently, the first two modes of both PODs, illustrated in Fig.…”
Section: Podmentioning
confidence: 98%
“…In the current work, the distinction between the A-II and SA modes is maintained to aid discussion. Forced oscillation studies have shown that the wake can exhibit the A-IV mode (in which two pairs of counter-rotating vortices are shed per cycle; figure 1) at similar ranges of reduced velocity and vibration amplitude to that which are experienced by a cylinder in this region of the response regime (Ongoren & Rockwell 1988;Nishihara, Kaneko & Watanabe 2005;Konstantinidis, Balabani & Yianneskis 2007). Cagney & Balabani (2013b) showed that this mode can also occur in the wake of a freely vibrating cylinder; the mode was stable, and caused the second branch to occur in a slightly different form, with a lower-amplitude response compared with when the SA mode was present.…”
Section: Streamwise Response Regimementioning
confidence: 99%
“…The A-IV mode has been observed in studies in which a cylinder is forced to oscillate 17,25 or is placed in pulsating flow. 32 This mode is characterised by the shedding of four vortices per wake cycle, with a pair of counter-rotating vortices shed in each cylinder oscillation cycle (Figure 1), and has recently been shown to also occur in the wake of freely oscillating cylinders in the second response branch, 33 using the same experimental data presented in this paper. Wake modes are typically identified in flow-visualisation studies using dye 1,25,34 or laserinduced fluorescence.…”
Section: Introductionmentioning
confidence: 95%